PCS-17 The Potency Of Sernai Leaves (Wedelia biflora) to Increase Healing of contusion in Rats (Rattus norvegicus) - . Rinidar; L A Marzuki; E Safitri; M Isa; M Hasan; . Amiruddin; T M Lubis; . Hennivanda; A Hamzah; N Asmilia; A Sutriana (Hemera Zoa, 2018)
INTRODUCTION Contusion is a type of injury caused by a collision of the body with a blunt object followed by damage to the soft parts of the body, bone damage, bleeding and swelling. The tissue Injuries cause an inflammatory or inflammatory reaction, in which the inflammatory reaction is followed by pain (dolor), heat (kolor), red (rubor), swelling (tumor), and impaired function in the area around the wound (fungsiolesa). The Inflammatory reactions are the result of increased capillary permeability and migration of leukocytes to areas of inflamed tissue. The body's defense process against injury involves cells that infiltrate the wounded areas including neutrophils, macrophages, and lymphocytes. The body's response to inflammation is characterized by the release of neutrophils from the blood vessels which function as the first defense cells that play a role in phagocytosis of microorganisms and inflammatory cells in the wound. Contusion can be cured by giving anti-inflammatory drugs that aim to relieve pain, slow and prevent the spread of the tissue destruction process.the Anti-inflammatory drugs are classified into two, namely Non-Steroid Anti-inflammatory (NSAIDs) and Anti-inflammatory Steroids (AIS), a class of anti-inflammatory drugs that have the ability to suppress signs and symptoms of inflammation. The use of anti-inflammatory drugs in humans can cause side effects that are harmful to the body such as ulcers, cardiovascular diseases and osteoporosis, while fot the animals cause the difficulties due to the large variety of species. Therefore, herbal ingredients are developed, one of which is sernai (Wedelia biflora). Sernai has empirical benefits as a medicine for wounds and ulcers , sernai leaf water extracts as antipyretics, antitripanosoma, antimicrobials, antifungal, and anti-inflammatory agents.Sernai contains alkaloids, terpenoids, triterpenoids and flavonoids. The Flavonoid compounds can inhibit the release of arachidonic acid, secretion of lysozyme enzymes from neutrophil cells and endothelial cells and inhibit the proliferation phase and exudation phase of the inflammatory process. If the prostaglandin pathway is inhibited, the the occurrence of local blood vessel vasodilatation will reduces and so a leukocyte infiltration decreases, then it is replaced by macrophages that function to help endothelial cell formation and new blood vessels so that wound healing can take place quickly.